2021
DOI: 10.4236/oje.2021.114025
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Macroinvertebrate Species to Discern Pollution Levels in Aquatic Environment

Abstract: The World is transforming more rapidly than ever before as a result of urbanization and industrialization. Such unrelenting destruction of nature has surpassed the capacity of mother Earth to support the aquatic ecosystem. Apart from freshwater macroinvertebrate species, there is no single measure of declining freshwater ecosystem that can capture either the short and long-term changes or the trend of overall freshwater ecosystem health. In that regard, the macroinvertebrates and physico-chemical variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Statistical methods: Data were tested for normal distribution using the Shapiro-Wilk test for normality before applying the parametric tests. To detect the site's effects on Physicochemical variables, the General Linear Model (GLM) under ANOVA was applied 11 . A pairwise comparison based on the Tukeyʼs method was used 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Statistical methods: Data were tested for normal distribution using the Shapiro-Wilk test for normality before applying the parametric tests. To detect the site's effects on Physicochemical variables, the General Linear Model (GLM) under ANOVA was applied 11 . A pairwise comparison based on the Tukeyʼs method was used 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the less commonly used metrics that we chose, Weigel and Dimick [13] found that insect taxa richness had one of the highest inverse correlations with disturbance of 47 metric variations that they evaluated. Metrics that utilize tolerance values and/or functional feeding group (FFG) information are used by 96% of US state bioassessment programs [10] [29], and world-wide [16] [30]. Though not widely used, Weigel and Dimick [13] found that percent tolerant collector-gatherers (C-G) metric had a high correlation with disturbance.…”
Section: Choice Of Metrics and Indicesmentioning
confidence: 99%